PERAN PARTISIPASI MASYARAKAT, AKUNTABILITAS, DAN TRANSPARANSI DALAM MEWUJUDKAN GOOD GOVERNANCE TERHADAP PEMBANGUNAN DESA - Situmorang, Christina Verawaty; Simanjuntak, Arthur; Elisabeth, Duma M (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2020)
The objectives research to examine the influence of transparency, accountability, and society participation in the financial management of Rural Development. This research uses Survey method with questionnaire as the instrument. The population of the study was the entire apparatus and the Minister of Village fund managers. Based on the Purposive sampling method, the number of samples obtained is 75 respondents. The research used in this study is quantitative research with the aim of the study of the research in this literature with multiple regression tests and the validity and reliability test to determine Quality questionnaire used with SPSS software. The results of this study show that partials, accountability and society participation had positive significant influence on rural development. While the transparency variable had negative significant influence on rural development. Simultaneous transparency, accountability and society participation had positive influence on rural development. Kata Kunci: Transparansi, Akuntabilitas, Partisipasi Masyarakat dan Pembangunan Desa.